External Validation of UDCA Response Score in Slovak and Croatian Patients with Primary Biliary Cholangitis - Jakub Gazda; Martin Janicko; Sylvia Drazilova; Ivica Grgurevic; Tajana Filipec Kanizaj; Tomas Koller; Beatrica Bodorovska; Maja Mijic; Ivana Mikolasevic; Ivana Knezevic Stromar; Branislav Kucinsky; Matej Gazda; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background. Ursodeoxycholic acid response score (URS) is a prognostic model that estimates the baseline probability of treatment response after 12 months of ursodeoxycholic acid (UDCA) therapy in patients with primary biliary cholangitis (PBC). Aim. To independently evaluate the predictive performance of the URS model. Methods. We used a cohort of Slovak and Croatian treatment-naïve PBC patients to quantify the discrimination ability using the area under receiver operating characteristic curve (AUROC) and its 95% confidence interval (CI). Furthermore, we evaluated the calibration using calibration belts. The primary outcome was treatment response after 12 months of UDCA therapy defined as values of alkaline phosphatase ≤1.67 × upper limit of normal. Results. One hundred and ninety-four patients were included. Median pretreatment age was 56 years (interquartile range 49–62). Treatment response was achieved in 79.38% of patients. AUROC of the URS was 0.81 (95% CI 0.73–0.88) and the calibration belt revealed that response rates were correctly estimated by predicted probabilities. Conclusion. Our results confirm that the URS can be used in treatment-naïve PBC patients for estimating the treatment response probability after 12 months of UDCA therapy.